(untitled) (ModaPalavra e-periódico, 2012)
This paper encourages the exercise of reflection and understanding of contemporary thought from philosophical theories and concepts, relating the social transformations in the practice of Design and the emergence of sustainability. Understanding the vision of thinkers like Guattari, Deleuze, Katz, Morin, Bauman, Manzini, among others, as the Theory of Rhizomes, the Hybridity, the Complexity and Liquid Modernity are associated and require a global vision and interdisciplinary approach, by mainstreaming disciplines to the correct implementation of sustainability in design.